Comparison of out-of-hospital cardiac arrests during the COVID-19 pandemic with those before the pandemic: an updated systematic review and meta-analysis - Kim, Jae Hwan; Ahn, Chiwon; Park, Yeonkyung; Won, Moonho (Frontiers in Public Health, 2023)
The coronavirus disease of 2019 (COVID-19) pandemic, directly and indirectly, affected the emergency medical care system and resulted in worse out-of-hospital cardiac arrest (OHCA) outcomes and epidemiological features compared with those before the pandemic. This review compares the regional and temporal features of OHCA prognosis and epidemiological characteristics. Various databases were searched to compare the OHCA outcomes and epidemiological characteristics during the COVID-19 pandemic with before the pandemic. During the COVID-19 pandemic, survival and favorable neurological outcome rates were significantly lower than before. Survival to hospitalization, return of spontaneous circulation, endotracheal intubation, and use of an automated external defibrillator decreased significantly, whereas the use of a supraglottic airway device, the incidence of cardiac arrest at home, and response time of emergency medical service (EMS) increased significantly. Bystander CPR, unwitnessed cardiac arrest, EMS transfer time, use of mechanical CPR, and in-hospital target temperature management did not differ significantly. A subgroup analysis of the studies that included only the first wave with those that included the subsequent waves revealed the overall outcomes in which the epidemiological features of OHCA exhibited similar patterns. No significant regional differences between the OHCA survival rates in Asia before and during the pandemic were observed, although other variables varied by region. The COVID-19 pandemic altered the epidemiologic characteristics, survival rates, and neurological prognosis of OHCA patients.